2020
DOI: 10.30787/gaster.v18i1.326
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent Pelayanan Kebidanan di PMB Kecamatan Mantrijeron Yogyakarta

Abstract: Dalam melaksanakan praktik/kerja, bidan berkewajiban untuk memberikan informasi tentang masalah kesehatan pasien dan pelayanan yang dibutuhkan, meminta persetujuan tindakan yang akan dilakukan, melakukan pencatatan asuhan kebidanan dan pelayanan lainnya secara sistematis.. Tujuan penelitian ini adalah mengetahui pelaksanaan informed consent pelayanan kebidanan di praktik mandiri bidan Kecamatan Mantrijeron Yogyakarta. Metode penelitian yuridis sosiologis. Lembar persetujuan tindakan KB dari 7 rekam medic, 2 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…The ethical principles underlying informed consent between midwives and patients are enshrined in Law Number 17 of 2023 concerning Health Services. Justice, as the cornerstone principle, demands that information provided during the informed consent process is fair and equitable for all patients, regardless of their background (Pujiastuti & Kristiana, 2020). Furthermore, midwives are expected to avoid discrimination and provide appropriate explanations to every individual.…”
Section: Methodsmentioning
confidence: 99%
“…The ethical principles underlying informed consent between midwives and patients are enshrined in Law Number 17 of 2023 concerning Health Services. Justice, as the cornerstone principle, demands that information provided during the informed consent process is fair and equitable for all patients, regardless of their background (Pujiastuti & Kristiana, 2020). Furthermore, midwives are expected to avoid discrimination and provide appropriate explanations to every individual.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, based on the results of a documentation study at PMB on 7 KB medical records and ten labor medical records, it was found that for filling out the KB action approval sheet from 7 medical records/approval sheets, 2 of them were invalid because there was no signature on the action approval sheet while on the delivery approval sheet from 10 medical records, 4 of them did not have a midwife's signature. One witness must still sign the approval sheet (Pujiastuti & Kristiana, 2020). The results of previous studies state that the application of informed consent in PMB and other health facilities still needs to be implemented.…”
Section: Original Research Papermentioning
confidence: 99%
“…Sebuah studi menemukan 90% bidan praktek mandiri (BPM) kurang memberikan informasi dan meminta persetujuan tindakan pemasangan kontrasepsi (6). Studi lain menyatakan bahwa dari 7 pasien tindakan pemasangan kontrasepsi, bidan tidak menandatangani formulir persetujuan tindakan sebanyak 6 formulir dan 2 tidak terdapat tandatangan pasien (7).…”
unclassified